Targeting the INCENP IN-box–Aurora B interaction to inhibit CPC activity in vivo. Issue 11 (November 2014) - Gohard, Florence H.; St-Cyr, Daniel J.; Tyers, Mike; Earnshaw, William C.
Abstract : The chromosome passenger complex (CPC) is an essential regulator of mitosis and cytokinesis. The CPC consists of Aurora B kinase, inner centromere protein (INCENP), and the targeting subunits survivin and borealin/Dasra B. INCENP is a scaffolding subunit for the CPC and activates Aurora B via its conserved IN-box domain. We show that overexpression of soluble IN-box in HeLa cells affects endogenous CPC localization and produces a significant increase in multinucleated and micronucleated cells consistent with CPC loss of function. The dominant-negative effect of soluble IN-box expression depends on residues corresponding to hINCENP W845 and/or F881, suggesting that these are essential for Aurora B binding in vivo . We then screened a targeted library of small (five to nine residues long) circular peptide (CP) IN-box fragments generated using split intein circular ligation of proteins and peptides (SICLOPPS) methodology. We identified a number of CPs that caused modest but reproducible increases in rates of multinucleated and micronucleated cells. Our results provide proof of concept that inhibition of the Aurora B–IN-box interaction is a viable strategy for interfering with CPC function in vivo .